Gestão do conhecimento em agências do Banco do Brasil S. A.: estudo de caso em filiais localizadas na cidade de Curitiba, Estado do Paraná. - Bronislawski, Luiz Antonio (2002)
In this text we tried to make a critic analysis of knowledge management, by means of case studies about some branches of Banco do Brasil S.A., trying to identify the presence or absence of elements that characterize the environmental working place focused on a continuous learning. The research was taken at several branches of Banco do Brasil S.A. in Curitiba ¿ State of Paraná ¿ Brasil. We asked the managers to answer the questions as they represent the leadership in every branch. The critic points that interfere positive or negatively the daily activities on knowledge management were examined, such as: time, administration of the branches, market changings, information systems, knowledge generation and transmission, besides the internal and external standard rules. The conclusion is that knowledge management in the researched branches is still in its beginning. Although there is an advanced technical infra structure and the managers have demonstrated some knowledge on this subject and are aware of its .importance for the company. The knowledge management is visualized more as an auxiliary technology for the updated models than a new way of managing the organization. The most important revolution expected - to modify the way of thinking and acting of the employees - is still in its starting point.